Graduate Entry Nursing Students’ Well-Being and Transformation in Becoming Registered Nurses: Phase Three of a Longitudinal Case Study - Shannon, Kay; McClunie-Trust, Patricia; Macdiarmid, Rachel; Jarden, Rebecca; Dewar, Jan; Turner, Rosemary; Winnington, Rhona; Mowatt, Rebecca; Jones, Virginia (Elsevier BV, 2024)
Background Graduate entry nursing (GEN) programmes offer an accelerated entry to practice pathway for people with a non-nursing degree. Characteristics and motivations of students enrolling in these programmes differ from those in nursing undergraduate programmes. Aim To explore the experiences of students on completion of a graduate entry Master of Nursing Science degree. Methods We report the findings of phase three of a longitudinal study conducted at the completion of a GEN program. Semi-structured interview recordings were transcribed and analysed using reflexive thematic analysis. Reporting of the study followed the Consolidated Criteria for Reporting Qualitative Studies. Findings We constructed three themes, sustaining well-being, perceptions and misconceptions, and transformation. Sustaining well-being encompassed students navigating challenges in maintaining work/study/life balance, physical health, and psychological well-being. Perceptions and misconceptions included students developing an awareness of the reality of nursing, programme intensity, and negative perceptions of nursing as a career. Transformation transpired through the students learning and recognising what it takes to succeed and develop their professional identity. Discussion Participants balanced supporting well-being with the sacrifices that were required to complete a demanding accelerated programme. Their life and previous study experience supported development of their growing self-identity as nurses. Understanding the experiences of GEN students during the later stages of their entry to practice education provides an opportunity to understand their transition to the profession and inform both programme development and graduate nursing programmes. Conclusion Ensuring GEN students are supported to transition to practice will contribute to addressing the global nursing workforce shortage.
Keywords: 4203 Health Services and Systems; 4205 Nursing; 42 Health Sciences; 4 Quality Education; 1110 Nursing; Nursing; 3901 Curriculum and pedagogy; 4204 Midwifery; 4205 Nursing